(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article presents the transversal reading of 21 contemporary latin american novels, attending to define the basic features that this corpus presents as a sub-genre of the “nueva novela histórica” (new historical romance), which justifies the denomination of “nueva crónica de Indias” (new chronicle of Indias). The analysis is a re-elaboration of Seymour Menton and Fernando Aínsa’s works and proposes four main axes: (the) recurrence of determinated discursive types, (the) intertextuality, (the) carnavalization and (the) new definitions of the concepts of time and space, showing in each of them the different stylistic variations of this sort of narrative and reflecting on their particular vision of History, which is very close to the approach of the latin american “thinking of liberation”, that coincides temporarily with the emergence of this revisonistical literary proposal.